2018
DOI: 10.1002/eqe.3105
|View full text |Cite
|
Sign up to set email alerts
|

Seismic retrofitting of braced frame buildings by RC rocking walls and viscous dampers

Abstract: Summary A design procedure for seismic retrofitting of concentrically and eccentrically braced frame buildings is proposed and validated in this paper. Rocking walls are added to the existing system to ensure an almost uniform distribution of the interstorey displacement in elevation. To achieve direct and efficient control over the seismic performance, the design procedure is founded on the displacement‐based approach and makes use of overdamped elastic response spectra. The top displacement capacity of the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…In the recent past, several studies have suggested a combined approach to building renovation. Among all the possible combined intervention strategies, those that can be performed from the outside are more appealing [9][10][11][12], because they reduce the disruption to the occupants during the works and do not require their relocation. La Greca and Margani [4] have highlighted the advantages of combined renovation actions, indicating the barriers that currently limit such actions and suggesting possible countermeasures.…”
Section: The State Of Art Of Combined Retrofit Interventionsmentioning
confidence: 99%
“…In the recent past, several studies have suggested a combined approach to building renovation. Among all the possible combined intervention strategies, those that can be performed from the outside are more appealing [9][10][11][12], because they reduce the disruption to the occupants during the works and do not require their relocation. La Greca and Margani [4] have highlighted the advantages of combined renovation actions, indicating the barriers that currently limit such actions and suggesting possible countermeasures.…”
Section: The State Of Art Of Combined Retrofit Interventionsmentioning
confidence: 99%
“…In regard to the inelastic behaviour of braces in tension, some research studies have highlighted the importance of the flexural stiffness of the braced beams. 2,7,8 Indeed, flexible braced beams limit the inelastic elongation of braces under tension and sometimes prevent these members from yielding. Conversely, stiff beams ensure large plastic elongations and thus high energy dissipation prior to brace fracture.…”
Section: Introductionmentioning
confidence: 99%
“…However, the relative displacement caused by the added damping depends to a great extent on the properties of the adjacent structures, 11 so local strengthening of the existing slabs connected to the dampers may also be required 10 . Another alternative is the use of external post‐tensioned walls 12–17 and steel braced towers, 18,19 centrally pinned at the foundation to impose uniform interstorey drift along the height of the frame. It should be noted that the self‐weight of pinned rocking systems acts against stability, leading to permanent displacement unlike stepping rocking wall able to re‐centre because of gravity 20 .…”
Section: Introductionmentioning
confidence: 99%